The adsorption of Cu(II) ions by polyaniline grafted chitosan beads. - Igberase, Ephraim (Vaal University of Technology, 2013)
This work investigates the possible use of chitosan beads and polyaniline grafted chitosan beads (PGCB) for the adsorption of copper ions from copper contaminated water. For this purpose chitosan flakes were converted to chitosan beads. However, a variable from a number of reaction variables (aniline concentration, chitosan concentration, temperature, acid concentration, reaction time and initiator concentration) was varied while others was kept constant, in an attempt to determine the best conditions for grafting of polyaniline onto chitosan beads. Percentage (%) grafting and % efficiency were key parameters used to determine such conditions. The chitosan beads and PGCB were characterized using physical techniques such as Fourier transformed infra red (FTIR), X-ray diffraction (XRD), and scanning electron microscope (SEM). The beads were used as an adsorbent for copper ions removal. The effect of pH on the removal rate of copper (II) by PGCB was investigated on by varying the pH values from pH 3 to 8 at an initial concentration of 40 mg/l. The effect of contact time, initial concentration and temperature was also investigated. The Langmuir and Freundlich model were used to describe adsorption isotherms for chitosan beads and PGCB, with correlation coefficient (R2) as the determining factor of best fit model. The thermodynamics of adsorption of copper (II) onto PGCB was described by parameters such as standard Gibb’s free energy change (ΔGo), standard enthalpy change (ΔHo), and standard entropy change (ΔSo) while the pseudo first-order and pseudo second-order kinetic model was used to describe kinetic data for the PGCB, with R2 and chi- square test (  2) as the determinant factor of best fit model. From the desorption studies, the effect of eluants (HCl and HNO3) and contact time on percentage desorption of PGCB loaded copper (II) ion was investigated upon. In determining the reusability of the PGCB loaded copper (II) ion, three cycles of adsorption/desorption studies was carried out. The results obtained from determining the best conditions for grafting polyaniline onto chitosan beads revealed the following grafting conditions; [Aniline] 0.1 g/l, [temperature] 35oC, [chitosan] 0.45 g/l, [HCl] 0.4 g/l, [(NH4)2S2O8] 0.35 g/l, and [time] 1 h. These conditions were applied in the grafting of polyaniline onto chitosan beads. FTIR analysis showed increase intensity in the grafted beads which provided evidence of grafting, XRD measurement showed a decrease in crystallinity in the PGCB as against the partial crystalline nature of chitosan. In SEM analysis, evidence of grafting was revealed by the closed gap between the polysaccharide particles in the PGCB. From the investigation carried out on the effect of pH on the percentage removal of Cu(II) ions by PGCB, the optimal pH value was found to be pH 5 with a percentage removal of 100% and this value was used for all adsorption experiment. Also from the investigation performed on the effect of contact time and initial concentration, it was observed that there was a sharp increase in the amount of Cu(II) ions adsorbed by PGCB up until contact time of 30 min and thereafter, it increases gradually. From the experiment carried out on the effect of temperature on adsorption capacity, there was an increase in adsorption capacity with increase in temperature. Moreover, at temperatures of 25oC, 35 oC and 45oC the Langmuir model gave the best fit for the chitosan beads having R2 values that are equal and greater than 0.942 in contrast to Freundlich having R2 values that is equal and greater than 0.932. The maximum adsorption capacity (Qm) from Langmuir model at these temperatures were 30.3 mg/g, 47.6 mg/g and 52.6 mg/g respectively. Also, the Langmuir model gave the best fit for the PGCB having R2 values that are equal and greater than 0.956 in contrast to Freundlich model with R2 values that is equal and greater than 0.935. The Qm from Langmuir model at these temperatures were 80.3 mg/g, 90.9 mg/g and 100 mg/g respectively. The values of Qm for PGCB appears to be significantly higher when compared to that of chitosan beads and this makes PGCB a better adsorbent than chitosan beads. From the thermodynamic studies carried out on PGCB, the values of ΔGo were negative and this denotes that the adsorption of copper ions onto PGCB is favorable and spontaneous, the positive value of ΔHo shows the adsorption process is endothermic and the positive value of ΔSo illustrate increased randomness at the solid-liquid interface during the adsorption process. Also, from the kinetic studies carried out on the PGCB, the pseudo second-order kinetic model best described the kinetic data having R2 values that are equal and greater than 0.994 in contrast to the pseudo first-order kinetic model with R2 values that is equal and greater than 0.913. The  2 values for the pseudo first-order and pseudo second-order kinetic model were similar; however, there was a large difference for qe between the calculated (qeCal) values of the first-order kinetic model and experimental (qeExp) values. In the case of the pseudo second-order model, the calculated qe values agree very well with the experimental data. Desorption of the metal ions from PGCB was efficient. 0.5 M HCl was successfully used in desorbing the beads loaded with copper ions and a percentage desorption of 97.1% was achieved at contact time of 180 min. PGCB were successfully re-used for adsorption/desorption studies were a Qm of 83.3 mg/g, 83.3 mg/g and 76.9 mg/g was achieved in the first, second and third cycle respectively.
M. Tech. (Department of Chemical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Adsorption; Chitosan beads; Polyaniline grafted chitosan beads (PGCB); Copper ions; Copper contaminated water; Dissertations, Academic -- South Africa; Adsorption; Surface chemistry; Chemical kinetics; Copper -- Metallurgy; Copper ions -- Analysis